Long-term outcome of endovascular repair of thoracic and abdominal aortic diseases: a retrospective cohort study of 101 patients from a tertiary care centre - Rajesh Vijayvergiya; Basant Kumar; Lipi Uppal; Ashish Sharma; Ajay Savlania; Ankush Gupta; Harkant Singh; Manphool Singhal (Jornal Vascular Brasileiro)
Abstract Background Thoraco-abdominal endovascular aortic repair [(T)EVAR] of thoracic (TEVAR) and abdominal aorta (EVAR) has surpassed open surgical repair for thoraco-abdominal aortic diseases. Objectives We describe the long-term outcomes of 101 (T)EVAR patients treated over the last eleven years. Methods A retrospective analysis of 101 consecutive (T)EVAR patients was performed. The primary endpoints were in-hospital and 30-day outcomes, while the secondary endpoints were long-term outcomes and re-intervention rates. Results Out of 101 patients, EVAR and TEVAR were performed in 40 (39.6%) and 61 (60.3%) patients, respectively. Mean age was 58.04 ± 15.7 years. Technical success rates were 100% and 95% in the EVAR and TEVAR groups, respectively. Intraoperative endoleak was observed in 17 patients. Major perioperative complications (n=16) included retrograde aortic dissection (n=1), stent graft migration (n=2), paraparesis (n=1), device system entrapment in iliac vessels (n=1), acute renal failure (n=2), acute limb ischemia (n=3), and aorto-enteric fistula (n=2). The 30-day mortality rate was 7.9% (8 patients). Kaplan Meyer survival estimates at 1 and 5 years were 79% (95% CI 66.0-87.0, SE 0.053%) and 71% (95%CI 56.0- 81.0, SE 0.065%) for TEVAR and 84% (95% CI 67.0-92.0, SE 0.061%) and 69% (95%CI 46.0-83.0, SE 0.094%) for EVAR, respectively. Diabetes and smoking were associated with increased all-cause mortality in EVAR (p=0.018) and TEVAR (p=0.045) cases, respectively, following Cox regression analysis. Conclusions We observed favorable short- and long-term outcomes in 101 (T)EVAR patients, proving its safety and long-term efficacy for management of thoracoabdominal aortic disease.